THE INFLUENCE OF THE COMPLEXITY OF THE COVID-19 HANDLING TASK LOAD AND THE PROFESSIONALISM OF MEMBERS' WORK ON POLICE PERFORMANCE IN LAW ENFORCEMENT DURING THE COVID-19 HANDLING PERIOD AT THE KATINGAN POLICE - Adhy Heriyanto; Rediyono, Rediyono (Jurnal Ekonomi, 2021)
The Effect Of The Complexity Of The Duty Of Covid 19 Handling And The Work Professionalism e Of Members On Police Performance In Law Enforcement In The Time Of Handling Covid 19 At Polres Katingan, Under The Guidance Of Lanny Purnama Kosasi And H. M .Zaid Abdurakhman, 2021. The purpose of this study was to determine and analyze the effect of the complexity of the workload and professionalism of members simultaneously on the performance of the police, to determine and analyze the effect of the complexity of the workload and the professionalism of members partially on the performance of the police and to determine and analyze between the variables of the complexity of the task load and work professionalism. members who have a dominant influence on the performance of the police in law enforcement during the handling of Covid 19 at the Katingan Police Station, Central Kalimantan Province. The population of this study were members of the police force at the Katingan Police Station, Central Kalimantan Province, amounting to 290 people and the sample in this study was 74 respondents. The data processing technique uses quantitative methods with multiple regression analysis through SPSS. The results of the first hypothesis research that the complexity of the task load and the professionalism of members have a significant effect simultaneously on the performance of the police, the results of the second hypothesis that the variable complexity of the task load and the professionalism of the members have a significant effect on the performance of the police have a significant effect on the performance of the police. on the performance of the police in law enforcement during the handling of covid 19 at the Katingan Police, Central Kalimantan Province.